Pneumonia infection in mice reveals the involvement of the feoA gene in the pathogenesis of Acinetobacter baumannii. Issue 1 (1st January 2018) - Álvarez-Fraga, Laura; Vázquez-Ucha, Juan C.; Martínez-Guitián, Marta; Vallejo, Juan A.; Bou, Germán; Beceiro, Alejandro; Poza, Margarita
ABSTRACT: Acinetobacter baumannii has emerged in the last decade as an important nosocomial pathogen. To identify genes involved in the course of a pneumonia infection, gene expression profiles were obtained from A. baumannii ATCC 17978 grown in mouse infected lungs and in culture medium. Gene expression analysis allowed us to determine a gene, the A1S_0242 gene ( feoA ), over-expressed during the pneumonia infection. In the present work, we evaluate the role of this gene, involved in iron uptake. The inactivation of the A1S_0242 gene resulted in an increase susceptibility to oxidative stress and a decrease in biofilm formation, in adherence to A549 cells and in fitness. In addition, infection of G. mellonella and pneumonia in mice showed that the virulence of the Δ0242 mutant was significantly attenuated. Data presented in this work indicated that the A1S_0242 gene from A. baumannii ATCC 17978 strain plays a role in fitness, adhesion, biofilm formation, growth, and, definitively, in virulence. Taken together, these observations show the implication of the feoA gene plays in the pathogenesis of A. baumannii and highlight its value as a potential therapeutic target.